Vanadium-doped modified ferric sodium pyrophosphate material based on spray drying as well as preparation method and application of vanadium-doped modified ferric sodium pyrophosphate material
The preparation of vanadium-doped modified sodium ferro pyrophosphate material by spray drying solves the shortcomings of the material in synthesis and conductivity, and significantly improves its reversible sodium storage capacity and cycle life.
Patent Information
- Application Number
- CN202311732705.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-12-15
AI Technical Summary
Sodium ferric pyrophosphate phosphate materials are sensitive to synthesis conditions and are difficult to synthesize pure phases. They have low electronic conductivity and ionic conductivity, resulting in problems such as low reversible specific capacity, poor rate performance, and large polarization voltage.
Spray drying method is used to prepare vanadium-doped modified sodium ferro pyrophosphate material. By preparing a uniform and stable complex ion solution, atomic mixing of vanadium and iron is promoted, forming a porous spherical morphology and broadening the sodium ion transport channel.
It significantly improves the reversible sodium storage capacity of the material, improves the cycle life, reduces the polarization voltage of the cycle process, and improves the rate performance.
Smart Images

Figure CN119569015A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a spray-dried vanadium-doped modified sodium iron phosphate pyrophosphate material, a preparation method and an application thereof. Background Art
[0002] Sodium-ion batteries have high potential and competitiveness in large-scale energy storage applications due to their abundant element reserves, low cost, and environmental friendliness. Among the positive electrode materials for sodium-ion batteries, polyanionic compounds have attracted widespread attention due to their higher electrode potential, strong structural framework, and rapid sodium ion deintercalation kinetics. Among them, sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2P2O7) is one of the positive electrode materials for sodium-ion batteries with relatively promising industrialization prospects. It combines the advantages of NaFePO4 and Na2FeP2O7, and has the advantages of low cost, good structural stability, high theoretical specific capacity, and long cycle life. However, this material is sensitive to synthesis conditions, it is difficult to synthesize pure phases, and the electronic conductivity and ionic conductivity are low. Problems such as low reversible specific capacity, poor rate performance, and large polarization voltage often occur.
[0003] Doping and carbon coating can improve the above problems. A Chinese patent (patent publication number: CN116750745A) discloses an iron-manganese-based composite phosphate material, which improves the reversible capacity by adjusting the Fe / Mn ratio, and at the same time improves the charge and discharge voltage platform, effectively improving the energy density of the material. However, due to the serious distortion of Mn during the charge and discharge process, the rate performance and cycle performance of the material are poor. A Chinese patent (patent publication number: CN115101738A) discloses a Na4Fe 1.5-1.5x V 1+x(PO4)2P2O7 material, it is believed that vanadium doping can provide certain lattice defects, and the doped material has better rate performance and cycle stability. However, the crystallinity and capacity of the vanadium-doped sodium iron phosphate pyrophosphate material prepared by this method are not ideal. Domestic and foreign researchers have used various carbon coating methods to improve the conductivity of sodium iron phosphate pyrophosphate, such as using graphene oxide to coat to form uniform microspheres, which greatly improves the rate performance of the material (Yuan T, Wang Y, Zhang J, et al. 3D graphene decorated Na4Fe3(PO4)2(P2O7)microspheres as low-cost and high-performance cathode materials for sodium-ion batteries[J]. Nano Energy, 2019, 56: 160-168.). However, this method can only improve the electronic conductivity of the material surface, but cannot improve the intrinsic conductivity of the material; at the same time, conductive materials such as graphene are expensive and not suitable for large-scale production. Summary of the invention
[0004] In view of the current problems of low reversible capacity and poor rate performance of sodium ferric phosphate pyrophosphate, the present invention proposes a vanadium-doped modified sodium ferric phosphate pyrophosphate material based on spray drying, as well as its preparation method and application. The atomic-level mixing of vanadium and iron is promoted by preparing a uniform and stable complex ion solution; the complex ion solution uses a weakly acidic aqueous solution as a solvent, which, on the one hand, promotes the formation of a uniform and stable ion complex solution; on the other hand, the volatilization of the acidic base liquid during the rapid drying process promotes the formation of a porous spherical morphology, and the preparation method is simple and controllable. The vanadium-doped sodium ferric phosphate pyrophosphate positive electrode material prepared by the spray drying method has good crystallinity and uniformity. Vanadium doping brings corresponding sodium vacancies, broadens the sodium ion transmission channel of the positive electrode material in the b-axis direction, thereby activating more active sodium sites, and significantly improves the reversible sodium storage capacity of the positive electrode material. At the same time, the excellent crystallinity and sodium vacancies also improve the cycle life of the sodium ferric phosphate pyrophosphate positive electrode material and reduce the polarization voltage during the cycle process.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A spray-dried vanadium-doped modified sodium iron phosphate pyrophosphate material having a porous spherical morphology and a particle size between 1 and 10 microns; its chemical formula is: Na 4-x Fe 3-x V x (PO4)2P2O7, where 0<x≤0.1.
[0007] Sodium iron phosphate pyrophosphate itself has high requirements for the synthesis environment and sintering temperature. Sodium iron phosphate and sodium iron pyrophosphate are prone to mixed phases during the sintering process, so the choice of synthesis method is very critical. The key to synthesizing pure phases is the uniform mixing of the elements in the precursor. It is difficult to achieve the requirements by solid-phase ball milling alone, and the spray drying method can achieve atomic-level mixing of each element with the help of a solution system, so the preparation of a uniform and stable complex ion solution is very important. The present invention selects a weakly acidic aqueous solution as a solvent, and the main purpose is to: on the one hand, promote the formation of a uniform and stable ion complex solution; on the other hand, utilize the volatility of weakly acidic molecules to obtain a porous morphology during rapid drying, thereby increasing the wetting area of the material and the electrolyte and shortening the sodium ion transmission channel. Suitable complexing agents and solution types are the prerequisites for forming a uniform and stable solution. Iron ions are easy to form precipitations with various phosphates and pyrophosphates, resulting in difficulty in phase formation and many impurities in phase formation. Adding complexing agents such as oxalic acid to the system can effectively solve the problem and obtain a uniform and stable complex ion solution. In addition, the solution is dispersed into micron-sized droplets during the spray drying process and dried rapidly during the heating process, which not only successfully granulates, but also avoids the stratification or even phase separation of the solution during the long drying process in the direct drying method. The type and content of doped ions are also very important: the ionic radius of vanadium ions and iron ions are similar, and both belong to the third period transition metal elements, so vanadium ions can enter the bulk phase of the material relatively smoothly. Trace doping of x≤0.1 reduces the disturbance to the original system and does not destroy the pure phase structure of the original material. The vanadium-doped sodium iron phosphate pyrophosphate positive electrode material prepared by spray drying has good crystallinity. Vanadium doping brings certain sodium vacancies, broadens the sodium ion transmission channel of the positive electrode material in the b-axis direction, thereby activating more active sodium sites and significantly improving the reversible sodium storage capacity. At the same time, the excellent crystallinity and sodium vacancies improve the cycle life of the sodium iron phosphate pyrophosphate positive electrode material and reduce the polarization voltage during the cycle process.
[0008] Specifically, the present invention provides a method for preparing a vanadium-doped modified sodium iron pyrophosphate material based on spray drying, comprising the following steps:
[0009] S1. Weigh a sodium source, an iron source, a vanadium source, and a phosphorus source according to a stoichiometric ratio, add them to a weakly acidic aqueous solution, stir them thoroughly to form a precipitate, and add a complexing agent to form a uniform and stable complex ion solution;
[0010] S2. Spray-drying the above solution into a precursor powder, and pre-sintering the precursor powder at a low temperature under a protective atmosphere to form a pre-sintered powder.
[0011] S3, fully mixing the pre-calcined powder and the carbon source and drying the mixture, sintering the mixture under a protective atmosphere, and cooling the mixture to obtain vanadium-doped sodium iron phosphate pyrophosphate.
[0012] Preferably, the weakly acidic aqueous solution in step S1 is a mixed solution of a weak acid and deionized water, and its concentration is 0.5-8 mol / L; the weak acid is one of acetic acid, formic acid, and propionic acid, preferably an acetic acid solution; and the solid-liquid ratio in the complex ion solution is 100-300 g / L.
[0013] Preferably, in step S1, the complexing agent is one or more of anhydrous oxalic acid, oxalic acid dihydrate, disodium ethylenediaminetetraacetic acid, citric acid, and ethylenediaminetetraacetic acid. The sodium source is at least one of sodium pyrophosphate, trisodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, disodium dihydrogen pyrophosphate, sodium carbonate, sodium bicarbonate, sodium oxalate, and sodium citrate; the iron source is at least one of ferric nitrate, ferric phosphate, ferrous oxalate, ferrous oxalate, and ferrous acetate; the vanadium source is at least one of ammonium metavanadate, vanadium oxalate, and vanadium pentoxide; the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and monosodium trihydrogen pyrophosphate; the relative amount ratio of the sodium, iron, vanadium, and phosphorus elements is 4-x:3-x:x:4 (0<x≤0.1).
[0014] Preferably, the spray drying parameters in step S2 are: injection volume of 100-400 mL / h, air inlet temperature of 130-200° C., and air outlet temperature of 80-150° C.
[0015] Preferably, the sintering temperature in step S2 is 200-350°C, and the sintering time is 1-4 hours; the sintering temperature in step S3 is 450-550°C, and the sintering time is 2-12 hours; the protective atmosphere in steps S2 and S3 is one of nitrogen, argon, and argon-hydrogen mixed gas (0.1-5% v / v hydrogen).
[0016] Preferably, the carbon source in step S3 is at least one of oleic acid, citric acid, graphite, and carbon nanotubes; and the relative amount ratio of the pre-calcined powder to the carbon source is 5:1 to 20:1.
[0017] The present invention also provides a vanadium-doped modified sodium iron phosphate pyrophosphate material prepared by the spray drying method.
[0018] The present invention also provides the use of the vanadium-doped modified sodium iron phosphate pyrophosphate material prepared by the spray drying method as a positive electrode material in a sodium ion battery. 4-x Fe 3-x V x (PO4)2P2O7 as a positive electrode material for sodium ion batteries has the advantages of low price, environmental friendliness and cycle stability compared to existing positive electrode materials such as transition metal oxides, Prussian blue and vanadium phosphates.
[0019] The present invention has the following beneficial effects:
[0020] (1) The present invention prepares a uniform and stable complex ion solution to achieve full mixing of vanadium and iron at the atomic level, and simultaneously uses rapid drying to avoid stratification or even phase separation of the solution during a long drying process; combined with a segmented sintering process and a carbon coating process, the phase formation reaction is fully carried out, and a pure phase material with good crystallinity is obtained.
[0021] (2) The present invention successfully granulates by a spray drying method. The weakly acidic aqueous solution is used as a solvent so that the particles obtained by spray drying have a porous structure left by the volatilization of a large number of acid molecules; the addition of vanadium changes the complex structure of the solution, so that the prepared vanadium-doped sodium iron phosphate pyrophosphate material has a uniform porous spherical structure.
[0022] (3) The vanadium-doped sodium iron phosphate pyrophosphate cathode material prepared by the spray drying method has good crystallinity. Vanadium doping brings certain sodium vacancies, which broadens the sodium ion transmission channel of the cathode material in the b-axis direction, thereby activating more active sodium sites and significantly improving the reversible sodium storage capacity. At the same time, the excellent crystallinity and sodium vacancies improve the cycle life of the iron phosphate pyrophosphate cathode material and reduce the polarization voltage during the cycle process.
[0023] (4) The sodium source, iron source, phosphorus source and carbon source used in the present invention are widely available and inexpensive. The spray drying method is simple and can quickly prepare kilogram-level precursors. The calcination temperature is low and the energy consumption is low. At the same time, trace vanadium doping has little effect on the cost, which is conducive to large-scale industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the scanning electron microscope image of Comparative Example 1.
[0025] Figure 2 This is a scanning electron microscope image of Example 2.
[0026] Figure 3 The X-ray diffraction patterns of Example 1 and Comparative Examples 3 and 4 are shown.
[0027] Figure 4 The specific capacity-voltage curves of Example 1 and Comparative Example 2 during charge and discharge are shown.
[0028] Figure 5 This is the rate performance diagram of Example 1.
[0029] Figure 6 This is the cycle performance diagram of Example 1 at 5C.
[0030] Table 1 shows the electrochemical data of Examples 1-2 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The experimental methods in the following embodiments without specifying specific conditions are selected according to conventional methods and conditions, or according to the product instructions.
[0032] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0033] Example 1
[0034] The chemical formula of the vanadium-doped sodium iron pyrophosphate material prepared by spray drying in this embodiment is Na 3.9 Fe 2.9 V 0.1 (PO4)2P2O7, the specific preparation method is:
[0035] S1. Weigh 0.05 mol sodium pyrophosphate, 0.1 mol ammonium dihydrogen phosphate, 0.145 mol ferric nitrate nonahydrate, and 0.005 mol ammonium metavanadate respectively and add them to 2 mol / L acetic acid solution. Stir thoroughly to form a white suspension. Add anhydrous oxalic acid to form a uniform and stable clear solution. The solid-liquid ratio is 150 g / L.
[0036] S2, spray drying the above solution into a precursor powder under the conditions of an injection rate of 200 mL / h, an inlet temperature of 130° C., and an outlet temperature of 90° C., and sintering the precursor powder at 300° C. for 1.5 h in an argon atmosphere to form a pre-calcined powder;
[0037] S3, the pre-sintered powder and oleic acid (the molar ratio is 10:1) are fully stirred and mixed in acetone and dried, and the mixture is sintered at 500°C for 10 hours in an argon-hydrogen mixed gas (5% hydrogen) atmosphere, and cooled to obtain vanadium-doped Na 3.9 Fe 2.9 V 0.1 (PO4)2P2O7 positive electrode material.
[0038] Example 2
[0039] The chemical formula of the vanadium-doped sodium iron pyrophosphate material prepared by spray drying in this embodiment is Na 3.95 Fe 2.95 V 0.05 (PO4)2P2O7, the preparation method is the same as that in Example 1, except that the stoichiometric ratio is adjusted, wherein the contents of different raw materials are: 0.05 mol sodium pyrophosphate, 0.1 mol ammonium dihydrogen phosphate, 0.1475 mol ferric nitrate nonahydrate, and 0.0025 mol ammonium metavanadate.
[0040] Comparative Example 1
[0041] The chemical formula of the vanadium-doped sodium iron pyrophosphate material prepared by spray drying in this embodiment is Na 3.9 Fe 2.9 V 0.1 (PO4)2P2O7 is prepared by ball milling followed by spray drying and granulation. The specific preparation method is as follows:
[0042] S1. Weigh 0.05 mol sodium pyrophosphate, 0.1 mol ammonium dihydrogen phosphate, 0.145 mol ferric nitrate nonahydrate, 0.005 mol ammonium metavanadate and 50 mL acetone respectively, mix them, and ball mill them at a speed of 400 r for 8 h to obtain a precursor mixture.
[0043] S2, spray drying the mixed solution into a precursor powder at an injection rate of 200 mL / h, an inlet temperature of 100° C., and an outlet temperature of 60° C., and sintering the precursor powder at 300° C. for 1 h in an argon atmosphere to form a pre-calcined powder;
[0044] S3, the pre-sintered powder and oleic acid (the molar ratio is 10:1.5) are fully stirred and mixed in acetone and dried, and the mixture is sintered at 500°C for 10 hours in an argon-hydrogen mixed gas (5% hydrogen) atmosphere, and cooled to obtain vanadium-doped Na 3.9 Fe 2.9 V 0.1 (PO4)2P2O7 positive electrode material.
[0045] Comparative Example 2
[0046] In this comparative example, the spray drying method is used to prepare undoped vanadium Na4Fe3(PO4)2P2O7 as a control material. The preparation method is the same as that in Example 1, except that the stoichiometric ratio is adjusted and vanadium is not contained. The contents of different raw materials are: 0.05 mol sodium pyrophosphate, 0.1 mol diammonium phosphate, and 0.15 mol ferric nitrate nonahydrate.
[0047] Comparative Example 3
[0048] In this comparative example, Na4Fe3(PO4)2P2O7 without vanadium doping was prepared by direct drying method as a control material, and the specific preparation method is as follows:
[0049] S1. Weigh 0.05 mol sodium pyrophosphate, 0.1 mol ammonium dihydrogen phosphate, 0.15 mol ferric nitrate nonahydrate and 0.075 mol citric acid respectively and add them to 2 mol / L acetic acid solution. After sufficient stirring, add appropriate amount of anhydrous oxalic acid to form a clear solution with a solid-liquid ratio of 150 g / L.
[0050] S2, drying the above solution in a 60° C. forced air oven and grinding the solution to obtain a precursor powder;
[0051] S3. The precursor powder is placed in an argon atmosphere and sintered at 300°C for 3 hours, then heated to 500°C and sintered for 10 hours, and then cooled to obtain Na4Fe3(PO4)2P2O7 prepared by the direct drying method.
[0052] Comparative Example 4
[0053] In this comparative example, the chemical formula of the vanadium-doped sodium iron pyrophosphate material prepared by solid phase ball milling is Na 3.9 Fe 2.9 V 0.1 (PO4)2P2O7, the specific preparation method is:
[0054] S1. Weigh 0.05 mol sodium pyrophosphate, 0.1 mol ammonium dihydrogen phosphate, 0.145 mol ferric nitrate nonahydrate, 0.005 mol ammonium metavanadate, 0.005 mol oleic acid and 50 mL acetone in a ball mill, mill at a speed of 400 r for 8 h, and then dry to obtain a precursor powder.
[0055] S2, the precursor powder was placed in an argon atmosphere and sintered at 300 ° C for 1.5 h, then heated to 500 ° C and sintered for 10 h, and then cooled to obtain Na prepared by solid phase ball milling 3.9 Fe 2.9 V 0.1 (PO4)2P2O7.
[0056] The materials made in the above embodiments and comparative examples are used as positive electrode materials in sodium ion batteries; more specifically, the above materials, conductive carbon black and PVDF are mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) is added as a diluent. After sufficient grinding, a uniform slurry is formed, and the slurry is coated on a carbon-coated aluminum foil current collector and dried as a test electrode. A button cell is assembled with a metal sodium sheet as the counter electrode; the electrolyte system used is 1M NaPF6 / DEGDME. It should be noted that both ether and carbonate electrolyte systems are used, and different electrolytes have little effect on the reversible capacity of this material. The electrolyte system given in this article has the best relative cycle performance; the diaphragm is a glass fiber diaphragm, and the electrochemical performance is tested using the Xinwei test system.
[0057] Initial specific capacity test conditions: 0.1C, 1.7-3.9V test; Note: 1C = 128mA / g.
[0058] Rate performance test conditions: 0.1C test for 3 weeks, 0.5C test for 3 weeks, 1C test for 3 weeks, 2C test for 3 weeks, 5C test for 3 weeks, 10C test for 3 weeks, 20C test for 3 weeks; Note: 1C = 128mA / g.
[0059] Cyclic performance test conditions: 5C, room temperature test for 500 cycles; Note: 1C = 128mA / g.
[0060] Figure 1 and 2 The scanning electron microscope images of Comparative Example 2 and Example 1 respectively show that the sodium iron pyrophosphate material without vanadium doping is basically in fragmented form, with a large number of pores on the surface caused by the evaporation and decomposition of acetic acid and oxalic acid; while vanadium doping enhances the solvation and complexing ability of the solution, and the particles have a good porous spherical structure after spray drying.
[0061] The X-ray diffraction spectra of the materials obtained in Example 1 and Comparative Examples 3 and 4 are as follows: Figure 3 As shown, it can be seen from the spectrum that the materials prepared by direct drying or solid phase ball milling contain a large amount of impurities, the main component of which is NaFePO4, which has no electrochemical activity. However, the vanadium-doped sodium iron phosphate pyrophosphate material prepared by spray drying did not produce any impurities and had good crystallinity. This shows that a small amount of vanadium doping will not change the crystal configuration of the material, nor will it produce new impurities, but a small peak shift will occur, further verifying that vanadium has been successfully incorporated into the material. Through simple lattice constant calculations, it was found that the lattice constant b of sodium iron phosphate pyrophosphate increased slightly after vanadium doping. In the sodium iron phosphate pyrophosphate material, sodium ions have a very complete and clear transmission channel on the b-axis, and the increase in the lattice constant b will be beneficial to the transmission of sodium ions along the b-axis.
[0062] The comparison of the charge and discharge curves of Example 1 and Comparative Example 2 at 0.1C is shown in the figure below: Figure 4 As shown in Figure 1, after adding a trace amount of vanadium, the reversible capacity of the material has been significantly improved, and the charging polarization voltage has decreased. The rate performance diagram of Example 1 at 0.1-20C is shown in Figure 1. Figure 5 As shown in the figure, the reversible capacity can reach 104.8 mAh / g at a current density of 1C; even under a fast charge and discharge condition of 20C, the material doped with trace amounts of vanadium can still maintain a high reversible capacity of 87 mAh / g. Figure 6 As shown, the material has a capacity retention rate of 98.2% in the first 500 cycles, showing excellent cycling performance.
[0063] The electrochemical data of Examples 1 to 2 and Comparative Examples 1 to 4 are summarized in Table 1. It can be seen from the table that the reversible capacity and cycle performance of vanadium-doped sodium iron phosphate pyrophosphate prepared by the complex ion solution spray drying method have been effectively improved. Comparative Example 1 mixed the raw materials by ball milling and then spray dried. The reversible capacity was slightly lower than that of the complex ion solution mixing method, indicating that the ball milling method can achieve a certain degree of element mixing, but the degree of mixing uniformity is not as good as that of the complex ion solution mixing method. Comparison of Comparative Example 1 and Comparative Example 4 shows that spray drying is the key to forming a pure phase. Comparative Examples 3 and Comparative Examples 4 do not use spray drying to prepare materials, which seriously affects the phase formation of the material and introduces a large number of non-electrochemically active impurities, resulting in a sharp decrease in the reversible capacity of the material.
[0064] Table 1: Electrochemical data of various examples and comparative examples
[0065]
[0066] The technical features of the above-mentioned embodiments can be combined arbitrarily, and the description of the embodiments is only used to help understand the method and core idea of the present application; as long as there is no contradiction in the combination of these technical features, they should be considered as the scope recorded in this specification. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A vanadium-doped modified sodium iron pyrophosphate material based on spray drying, characterized in that: Pure Na 4- x Fe 3-x V x (PO4)2P2O7 porous spherical granular material, wherein 0<x≤0.
1.
2. The method for preparing the vanadium-doped modified sodium iron pyrophosphate material based on spray drying according to claim 1, characterized in that: The material is prepared based on a spray drying method, and the preparation method comprises the following steps: S1. Weigh a sodium source, an iron source, a vanadium source, and a phosphorus source according to a stoichiometric ratio, add them to a weakly acidic aqueous solution, stir them thoroughly to form a precipitate, and add a complexing agent to form a uniform and stable complex ion solution; S2, spray drying the above solution into a precursor powder, and pre-sintering the precursor powder at a low temperature under a protective atmosphere to form a pre-sintered powder; S3, fully mixing the pre-calcined powder and the carbon source and drying the mixture, sintering the mixture under a protective atmosphere, and cooling the mixture to obtain the vanadium-doped modified sodium iron pyrophosphate material.
3. The method for preparing the vanadium-doped modified sodium iron pyrophosphate material based on spray drying according to claim 2, characterized in that: In step S1, the weak acid aqueous solution is a mixed solution of weak acid and deionized water, and its concentration is 0.5-8 mol / L; the weak acid is one of acetic acid, formic acid and propionic acid; the solid-liquid ratio in the complex ion solution is 100-300 g / L.
4. The method for preparing the vanadium-doped modified sodium iron pyrophosphate material based on spray drying according to claim 2, characterized in that: In step S1, the complexing agent is one or more of anhydrous oxalic acid, oxalic acid dihydrate, disodium ethylenediaminetetraacetic acid, citric acid, and ethylenediaminetetraacetic acid; the sodium source is at least one of sodium pyrophosphate, trisodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, disodium dihydrogen pyrophosphate, sodium carbonate, sodium bicarbonate, sodium oxalate, and sodium citrate; the iron source is at least one of ferric nitrate, ferric phosphate, ferrous oxalate, ferrous oxalate, and ferrous acetate; the vanadium source is at least one of ammonium metavanadate, vanadium oxalate, and vanadium pentoxide; the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, trisodium monohydrogen pyrophosphate, disodium dihydrogen pyrophosphate, and monosodium trihydrogen pyrophosphate; and the relative amount ratio of the corresponding elements in the sodium, iron, vanadium, and phosphorus sources is 4-x:3-x:x:4, wherein 0<x≤0.
1.
5. The method for preparing the vanadium-doped modified sodium iron pyrophosphate material based on spray drying according to claim 2, characterized in that: The spray drying parameters in step S2 are: injection volume of 100-400 mL / h, air inlet temperature of 130-200° C., and air outlet temperature of 80-150° C.
6. The method for preparing the vanadium-doped modified sodium iron pyrophosphate material based on spray drying according to claim 2, characterized in that: In step S2, the pre-sintering temperature is 200-350°C, and the sintering time is 1-4 hours; in step S3, the sintering temperature is 450-550°C, and the sintering time is 2-12 hours; in steps S2 and S3, the protective atmosphere is one of nitrogen, argon, and argon-hydrogen mixed gas (0.1-5% v / v hydrogen).
7. The method for preparing the vanadium-doped modified sodium iron pyrophosphate material based on spray drying according to claim 2, characterized in that: In step S3, the carbon source is at least one of oleic acid, citric acid, graphite, and carbon nanotubes; and the relative amount ratio of the pre-calcined powder to the carbon source is 5:1 to 20:
1.
8. A positive electrode sheet comprising the vanadium-doped modified sodium iron phosphate pyrophosphate material as claimed in claim 1 or obtained by the method as claimed in any one of claims 2 to 7.
9. A sodium ion battery, characterized in that: Contains the positive electrode sheet as claimed in claim 8.
Citation Information
Patent Citations
Modified iron-based pyrophosphate compound positive electrode material, preparation method and application of modified iron-based pyrophosphate compound positive electrode material in sodium ion battery
CN114695870A
Synthesis method of sodium ion battery positive electrode material phosphoric acid ferric pyrophosphate sodium / carbon
CN116443836A
Power type sodium ion negative electrode material for energy storage, battery, preparation method and application
CN116947016A
Vanadium-doped ferric sodium pyrophosphate / carbon composite material as well as preparation method and application thereof
CN117080392A
Novel Crop Fortification, Nutrition and Crop Protection Composition
US20190029266A1
Cited By
Sodium ferric pyrophosphate positive electrode material for sodium ion battery and preparation method of sodium ferric pyrophosphate positive electrode material
CN120589713A
A sodium-ion battery sodium ferrophosphate phosphate positive electrode material and a preparation method thereof
CN120589713B
Quickly synthesized ferric sodium pyrophosphate electrode material, preparation method thereof and positive electrode
CN121202094A
Non-stoichiometric ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN121202101A